PENAMPILAN REPRODUKSI KUDA BETINA PASCA PACU DI DESA PINABETENGAN RAYA KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA - Moningka, F A; Lapian, H; Paputungan, U; Turangan, S (ZOOTEC, 2016)
ABSTRACT Â  REPRODUCTION PERFORMANCE OF FORMER RACING FEMALE HORSE AT PINABETENGAN VILLAGE WEST TOMPASO DISTRICT OF MINAHASA REGENCY. Horse was the special animal to gain more money compare with any other animals. Breeding management related to reproduction of racing female horse must be taken intensively to produce a standard racing Indonesian horse called Indonesian racing horse (Kuda Pacu Indonesia, KPI). This study was conducted to evaluate reproduction performance of former racing female horse including first mating age, period time of estrus cycle, service per conception, foaling interval at Pinabetengan village, west Tompaso district of Minahasa regency. This village was a core area of farmer maintaining more racing horse in Minahasa regency. This study was done using purposive sampling method and focused on 103 former racing female horses as case study observation in obtaining primer data. The interview was also conducted to the owners of racing horse. Results showed that the averages of first mating age was 5.72 years, period time of estrus cycle was 21.67 days, service per conception was 1.65, and foaling interval was 11.98 months. Therefore, it can be concluded that former racing female horses at Pinabetengan village were included at good category of reproduction performance. Â  Key words: First mating age, estrus cycle period time, service per conception, foaling interval, Pinabetengan village Â